Pengaruh Kultur Teknis terhadap Serangan Penyakit pada Tanaman Oyong (Luffa Acutangula) di Desa Kuripan Kecamatan Empat Petulai Dangku - Arsi, Arsi; SHK, Suparman; Hamidson, Harman; Umayah, Abu; Gunawan, Bambang; Pujiastuti, Yulia; Pratama, Rahmat; Pratiwi, Fannia Aristika (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Arsi A, SHK Suparman, Hamidson H, Umayah A, Gunawan B, Pujiastuti Y, Pratama R, Pratiwi FA. 2022. The effect of technical culture on disease attacks on oyong (Luffa Acutangula) plants in Kuripan Village, Kecamatan Four Petulai Dangku. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1011-1022. Palembang: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI).The luffa plant/oyong is a fruit vegetable that is widely consumed by Indonesians in the form of fresh fruit The nutritional value of luffa is quite good because this fruit vegetable is a source of vitamins and minerals. Oyong plant is a climbing plant/vine. Oyong plants need a dry climate, with sufficient water availability throughout the season. Agricultural cultivation systems are never free from pests or diseases. In the field of farmers, there is not much knowledge about plant diseases or the causes of the disease itself. For this reason, this research practice aims to determine the effect of intercropping on disease attacks on Oyong (Luffa acutangula) plants. Field practice has been carried out in Kuripan Village, Empat Petulai Dangku District, Muara Enim Regency, South Sumatra Province from May to June 2022. The observation method used in this field practice is the direct observation method in the field which is carried out by determining the land, the land being taken has different cropping patterns. Then determine the plants to be sampled using the diagonal method. The data collected were primary data in the form of direct observation of symptoms in the field and secondary data obtained from farmer interviews. From the observation, there were 2 types of diseases, namely brown spots and virus mosaic.